PENGARUH TINGKAT PERPUTARAN MODAL DAN SKALA PERUSAHAAN TERHADAP PROFITABILITAS DI KOPERASI KSU PARIKESIT KARANGANYAR - Purwaningsih, Rully, Dra. Chuzaimah, M.M (2016)
This research was conducted in the Cooperative KSU Parikesitlocated in Karanganyar, Central Java. This research aimed at knowing the influences ofworking capital turnover ratio, cash turnover, account receivable turnover, customer amount growth, and employee amount on the profitability of a saving-and-loan cooperative in KSU ParikesitKaranganyar. This research used a quantitative approach. The method of data collection was conducted used the documentation method. The technique of data analysis used multiple regression analysis processed using the program of SPSS 19.0 for Windows. The results of the research showed that the working capital turnover ratio had a positive and significant influence on the profitability, the company scale had a negatively significant influence on the profitability, therefore, the working capital turnoverand the company scale had influence as much as 98.9% on the profitabilityof the company, meanwhile, the rest was influenced by other unknown factors.